A qualitative study to explore and identify reasons for dairy consumption and non-consumption among young adults (18–30 years old) in the UK and France - Caterina Franzon; Anestis Dougkas; Juliet Memery; Justine Prigent; Katherine M. Appleton (Journal of Nutritional Science)
The aim of this study was to explore and identify why young adults aged between 18 and 30 years in the UK and France do or do not consume dairy products. Several studies have associated dairy products with a healthy diet, and the production of soft dairy, i.e. milk, yoghurt, and soft cheese, as more environmentally friendly than some other animal-based products. Yet recent reports highlight that dairy intake is lower than recommended for health, especially among young adults. Using a qualitative methodology, forty-five participants aged 18–30 years (UK: n = 22; France: n = 23) were asked about their reasons for (non)consumption of a wide range of dairy products. Audio-recorded focus groups and individual interviews were conducted in English in the UK and in French in France, transcribed and coded. A thematic analysis found four themes and sixteen sub-themes (theme product-related: sub-themes sensory, non-sensory, composition; theme individual-related: sub-themes mode of consumption, preferences, personal reasons, knowledge, attitudes and concerns, needs or cravings; theme cultural aspects: sub-themes product categorization, social norms, use; theme market offering: sub-themes alternative, packaging, value for money, availability) to influence participants’ dairy (non)consumption in both countries. A seventeenth sub-theme (theme cultural aspects: sub-theme structure of the meal) was found to influence dairy consumption only in France. Further studies are needed to investigate these themes within larger samples, but these findings contribute to understanding dairy (non)consumption in young adults in the UK and France and may aid the development of strategies to improve young adults’ diets.